Features of tour product development for shore-excursion services for cruise ship passengers (Economics and region, 2023)
In the article the main approaches to the definition of the term "tour product" and "tour product for shore-excursion services for cruise ship passengers" are analysed. The article presents the process of development of a new tour product, which consists of the following main stages: analysis of the market of tourist services and the main suppliers in it; idea generation; development of tour product concept; formation of a tour product; formation of a tour product proposal for a cruise company. The requirements of cruise companies to the tour product for shore-excursion services are summarized. The main stages of the process of selection of a tour operator in the port of call by a cruise company are indicated. This approach to partner selection demonstrates the importance of close cooperation between cruise lines and tour operators in achieving a high standard of service and competitiveness in the cruise tourism market.
Keywords: cruise tourism; tour product; tour operator; cruise line; shore excursions